Effective treatment of Xanthelasma Palpebrarum with laser Er:YAG - Cleide Garbelini-Lima; Gabriela Evangelista de Almeida; Talita Fernandes Picanço e Souza; Alcidarta dos Reis Gadelha; Ilner de Souza e Souza (Sociedade Brasileira de Dermatologia (SBD), 2020)
Case study of exceptional response to treatment of recurrent xanthelasma palpebrarum with an ablative laser. The patient underwent a single session of laser Erbium: Yttrium-aluminum-garnet (Fotona®) 2940 nm, and we performed photographic records with Vectra® H2 2019 before and after the procedure. Satisfactory clinical results were reported, with good pain tolerability and early recovery compared to surgical procedures and, consequently, less time away from work activities.